Maternal effects on the genetic evaluation of Tabapuã beef cattle - José Elivalto Guimarães Campêlo; Paulo Sávio Lopes; Robledo de Almeida Torres; Luiz Otávio Campos da Silva; Ricardo Frederico Euclydes; Cláudio Vieira de Araújo; Carmen Silva Pereira (Genetics and Molecular Biology, 2004)
The aim of this investigation was to study the influence of maternal effects on the genetic evaluation of sire production in Tabapuã beef cattle. Single and multiple trait analyses were done with adjusted animal weights at 120, 240 and 420 days of age. Antagonism was observed between additive direct and maternal genetic effects, with the maternal effect being higher until weaning. The inclusion of maternal effects in the models removed part of the additive variance only in single trait analyses and resulted in smaller means and standard deviations for the sire breeding values. The use of maternal effect associated with single or multiple traits may affect sire ranking. The contradictory results of the single and multiple trait analyses for additive direct and maternal effects indicate that caution is needed when considering recommendations about the importance of maternal effects in Tabapuã beef cattle.